1987
DOI: 10.1002/ccd.1810130112
|View full text |Cite
|
Sign up to set email alerts
|

Catheter‐induced intimal injury during routine coronary catheterization in dogs

Abstract: The location and progression of changes in arterial permeability and structure were studied in nine dogs over a 13-week period following left coronary catheterization with standard coronary catheters. Changes in arterial permeability were analyzed by quantitating Evans blue dye (EBD) uptake over the aortic luminal surface (blue areas). Structural changes were assessed by light and electron microscopy. In the catheterized animals, compared to uncatheterized controls, we observed a significant increase in aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A possible explanation has recently been given by Lindner and Reidy [21] who showed an enhanced expression of platelet-derived growth factor B by endothelium of the leading edge up to 6 weeks after balloon injury of rat arteries. At the same time, more intimal hyperplasia was found underneath regenerating endothelium compared to the adjacent de nuded regions which could be explained by the disposi tion of platelet-derived growth factor B in the intimal layers since it is known to promote intimal lesion forma tion [22], During routine arterial cathctherization, large areas are denuded because of catheter manipulations [23], From the present study we infer that careful manipulation of a catheter may result in endothelial cell removal with out media necrosis, hence fast reendothelialization and relatively little intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation has recently been given by Lindner and Reidy [21] who showed an enhanced expression of platelet-derived growth factor B by endothelium of the leading edge up to 6 weeks after balloon injury of rat arteries. At the same time, more intimal hyperplasia was found underneath regenerating endothelium compared to the adjacent de nuded regions which could be explained by the disposi tion of platelet-derived growth factor B in the intimal layers since it is known to promote intimal lesion forma tion [22], During routine arterial cathctherization, large areas are denuded because of catheter manipulations [23], From the present study we infer that careful manipulation of a catheter may result in endothelial cell removal with out media necrosis, hence fast reendothelialization and relatively little intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Because transvascular nerve stimulation does not increase local wall temperature (18), lesions are probably due to catheter pressure against the wall. Similar lesions have been described for coronary angiography catheters (19). Thus, it seems reasonable to expect that the lesions may resolve, which needs to be proven during chronic experiments.…”
mentioning
confidence: 67%
“…On the other hand, the association between experimental endothelial denudation and atherosclerosis may have clinical relevance if the intimal surface suffers damage during clinical catheterization procedures that is comparable to that produced by balloon catheters. A previous study in dogs suggested that extensive endothelial denudation that involves over 70% of the aorta and proximal coronary luminal surfaces does occur as a consequence of catheter trauma during coronary angiography [ 5 ] . A similar degree of endothelial disruption was observed in the present study in the minipig whose size and arterial anatomy is comparable to that of man.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study in normal dogs has suggested that significant catheter-induced intimal injury, comparable to that associated with balloon injury noted above, can occur during routine coronary angiography [5]. In this study, we examined the impact of such clinical catheter injury on the progression of atherosclerosis over a 1 year period following routine coronary angiography in moderately hypercholesterolemic minipigs, which, unlike the dog, have been shown to develop humanoid atherosclerotic lesions.…”
Section: Introductionmentioning
confidence: 89%